Gene Variation at Immunomodulatory and Cell Adhesion Molecules Loci Impacts Primary Sjögren's Syndrome - Casadó-Llombart, Sergi; Gheitasi, Hoda; Ariño, Silvia; Consuegra-Fernández, Marta; Armiger-Borràs, Noelia; Kostov, Belchin; Ramos-Casals, Manuel; Brito-Zerón, Pilar; Lozano, Francisco (Frontiers in Medicine, 2022)
Primary Sjögren’s syndrome (pSS) is an autoimmune disease triggered by a combination of environmental and host genetic factors, which result in focal lymphocytic infiltration of exocrine glands causing eye and mouth dryness. Glandular infiltrates include T and B cell subsets positive for CD5 and/or CD6, two surface scavenger receptors involved in fine tuning of intracellular signals mediated by the antigen-specific receptor complex of T (TCR) and B (BCR) cells. Moreover, epithelial cells of the inflamed glands overexpress CD166/ALCAM, a CD6 ligand involved in homo and heterotypic cell adhesion interactions. All this, together with the reported association of functionally relevant single nucleotide polymorphisms (SNPs) of CD5, CD6 and CD166/ALCAM with risk or prognosis of some immune-mediated inflammatory disorders, led us to investigate similar associations in a local cohort of pSS patients. Logistic regression analyses of individual SNPs showed association of CD5 rs2241002T with anti-Ro/La positivity, CD6 rs17824933C with neutropenia, and CD6 rs11230563T with increased leukopenia and neutropenia but decreased peripheral nervous system ESSDAI. Further analyses showed association of haplotypes from CD5 (rs2241002T-rs2229177C) with anemia and thrombocytopenia, CD6 (rs17824933G-rs11230563C-rs12360861G) with cutaneous ESSDAI, and CD166/ALCAM (rs6437585C-rs579565A-rs1044243C and rs6437585C-rs579565G-rs1044243T) with disease susceptibility and several analytical parameters (anti-nuclear antibodies, neurological ESSDAI and hematologic cytopenias). These results support the relevance of gene variation at loci coding for cell surface receptors involved in modulation of T and B of lymphocyte activation (CD5, CD6) and epithelial-immune cell adhesion (CD166/ALCAM) in modulating clinical and analytical outcomes in pSS patients.